Beyond the Academic Gateway : Looking back on the Tenure-Track Journey - Handford, Victoria, 1957-; Sibbald, Timothy, 1966- (Book collections on Project MUSE., 2020)
"Tenure is a pivotal decision for the academy. If it is earned it provides security and permanence, creating further academic freedom to pursue research and interests important to the institution and to society. If it is not earned then the peer review process provides clarification for why it has not being earned. This book brings together lived experiences of academics around the time of the tenure decision. While the book is stand-alone, it has the same collection of authors who wrote about their tenure-track experiences in The Academic Gateway, making the pair of books a remarkable longitudinal collection. The authors in this book explore the complex relationship between academics, the academy as an ideal, and universities as an enactment of that ideal. Personal growth is evident and shows diversity of experience, as the maturing relationships with the role and workplace unfurl. Where tenure-track is a very personal journey, the period around tenure is necessarily a form of engagement with peers. Yet it has challenges, particularly in a milieu where academic freedom is being nurtured. Individual authors negotiate their choices between their personal objectives and institutional mandates and policies. Simultaneously, after years in the tenure-track, they continue to be evolving as academics, whether through personal growth or by seeking changes in the academy itself."--